2018
DOI: 10.1002/advs.201801007
|View full text |Cite
|
Sign up to set email alerts
|

Interfacially Induced Cascading Failure in Graphite‐Silicon Composite Anodes

Abstract: Silicon (Si) has been well recognized as a promising candidate to replace graphite because of its earth abundance and high‐capacity storage, but its large volume changes upon lithiation/delithiation and the consequential material fracturing, loss of electrical contact, and over‐consumption of the electrolyte prevent its full application. As a countermeasure for rapid capacity decay, a composite electrode of graphite and Si has been adopted by accommodating Si nanoparticles in a graphite matrix. Such an approac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
42
0
1

Year Published

2018
2018
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 73 publications
(49 citation statements)
references
References 54 publications
(66 reference statements)
4
42
0
1
Order By: Relevance
“…Thus, the rate of capacity fading at the initial cycling is closely connected with the characteristics of the Si, such as the size, the crystallinity, and the specific architecture for mitigating the Si‐based failure mechanism . Sufficient graphite is crucial for reducing the interparticle electrical resistance, despite the associated loss of specific capacity, otherwise the capacity fading would be accelerated, like with the Si electrode in which graphite is not blended …”
Section: Critical Factors For the Combination Of Graphite And Simentioning
confidence: 99%
“…Thus, the rate of capacity fading at the initial cycling is closely connected with the characteristics of the Si, such as the size, the crystallinity, and the specific architecture for mitigating the Si‐based failure mechanism . Sufficient graphite is crucial for reducing the interparticle electrical resistance, despite the associated loss of specific capacity, otherwise the capacity fading would be accelerated, like with the Si electrode in which graphite is not blended …”
Section: Critical Factors For the Combination Of Graphite And Simentioning
confidence: 99%
“…Meanwhile, the huge difference in the volume changes of graphite and Si during cycling would result in electrical contact loss for graphite, leading to additional deterioration. A recent investigation on Si/G composite revealed that graphite loses its intrinsic capacity after cycling, because the graphite particles become isolated from the electrical network due to the deterioration of the microstructure of the electrodes caused by volume expansion of the Si particles, cracks, and excessive SEI formation at the interface …”
Section: Challenge Of the Integration Of Silicon And Graphite Anodes mentioning
confidence: 99%
“…A recent investigation on Si/G composite revealed that graphite loses its intrinsic capacity after cycling, because the graphite particles become isolated from the electrical network due to the deterioration of the microstructure of the electrodes caused by volume expansion of the Si particles, cracks, and excessive SEI formation at the interface. 13 The repeated volume changes of Si during cycling process can seriously change the morphology of Si/G composite. It has been reported that the Si nanoparticles turn into nanoporous structure with very large surface area as a result of repeated cycling, which leads to electrode swelling with rearrangement of the electrode components, and thus disrupts the electrode.…”
Section: Integration Of Silicon and Graphite Anodes For High-energy Lmentioning
confidence: 99%
“…At a current density of 0.1 C, the cycle was 200 cycles, and the specific capacity remained at 740 mAh g −1 . Excessive electrolyte consumption causes rapid capacity decay …”
Section: Silicon‐based Composite Materialsmentioning
confidence: 99%